2022
DOI: 10.1002/ctm2.858
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell profiling guided combination therapy of c‐Fos and histone deacetylase inhibitors in diffuse large B‐cell lymphoma

Abstract: In this commentary on Wang, Wu, Xia, and colleagues, Clinical Translational Medicine, 2022, we sum up and discuss recent evidence on the regulation and relevance of the transcription factor c-FOS in diffuse large B cell lymphoma cells that are treated with epigenetic erasers of the histone deacetylase inhibitor family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For example, functional dysregulation of histone acetyltransferases has been associated with cancer development, including B-cell [45,46] and T-cell lymphomas [47,48]. In humans, histone modifier gene mutations have been associated with inferior progression-free survival time in patients with T-cell lymphomas [48], and it has been demonstrated that HDAC regulates the expression of BCL6, involved in cell survival and/or differentiation in B-cell lymphoma [49], and HDAC inhibitors have been tried as therapy in humans [50][51][52]. In CML, repression of p16 tumour suppressor gene is regulated by histone H3 acetylation in vitro [53].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…For example, functional dysregulation of histone acetyltransferases has been associated with cancer development, including B-cell [45,46] and T-cell lymphomas [47,48]. In humans, histone modifier gene mutations have been associated with inferior progression-free survival time in patients with T-cell lymphomas [48], and it has been demonstrated that HDAC regulates the expression of BCL6, involved in cell survival and/or differentiation in B-cell lymphoma [49], and HDAC inhibitors have been tried as therapy in humans [50][51][52]. In CML, repression of p16 tumour suppressor gene is regulated by histone H3 acetylation in vitro [53].…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Truly, other targets of HDACi might also dictate resistance. For example, a recent study using single-cell sequencing illustrates that c-FOS antagonizes HDACi-induced apoptosis and is upregulated in DLBCL cells surviving HDACi (Kr€ amer and Schneider, 2022;Wang et al, 2022).…”
Section: B Histone Deacetylase Inhibitors Can Correctmentioning
confidence: 99%